2016
DOI: 10.1128/jvi.02345-15
|View full text |Cite
|
Sign up to set email alerts
|

RNA Silencing May Play a Role in but Is Not the Only Determinant of the Multiplicity of Infection

Abstract: The multiplicity of infection (MOI), i.e., the number of viral genomes that infect a cell, is an important parameter in virus evolution, which for each virus and environment may have an optimum value that maximizes virus fitness. Thus, the MOI might be controlled by virus functions, an underexplored hypothesis in eukaryote Strong evidence supports the fact that, in nature, mixed rather than single viral infections may predominate in both plant and animal hosts (1, 2). Mixed infections result in a variety of v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 59 publications
0
9
0
Order By: Relevance
“…The interaction between viruses inside a host cell (as represented schematically in figure 2) can be highly influenced by the multiplicity of infection (MOI) that indicates the number of viral genomes present in the same cell (Gutiérrez et al, 2010). There are some indications that the MOI is controlled by virus-encoded functions, such as the suppression of RNA silencing mechanisms (Donaire et al, 2016). In mixed infections of N. benthamiana with two genotypes of TMV, it was observed that the MOI was higher at initial stages, and then changed (Gonzalez-Jara et al, 2009).…”
Section: Impact On Virusesmentioning
confidence: 99%
“…The interaction between viruses inside a host cell (as represented schematically in figure 2) can be highly influenced by the multiplicity of infection (MOI) that indicates the number of viral genomes present in the same cell (Gutiérrez et al, 2010). There are some indications that the MOI is controlled by virus-encoded functions, such as the suppression of RNA silencing mechanisms (Donaire et al, 2016). In mixed infections of N. benthamiana with two genotypes of TMV, it was observed that the MOI was higher at initial stages, and then changed (Gonzalez-Jara et al, 2009).…”
Section: Impact On Virusesmentioning
confidence: 99%
“…A long-standing unanswered question is that which co-opted host components are involved in VRC assembly that protect (+)RNA viruses during replication from the potent RNAi response. The protection provided by VRCs seems significant, because plant (+)RNA viruses could replicate and accumulate even in the absence of RNAi suppressors [ 51 , 52 ]. Moreover, the Dicer-like enzymes could not completely degrade the viral dsRNA in infected cells, indicating that the viral dsRNA enjoys significant protection during replication.…”
Section: Introductionmentioning
confidence: 99%
“…2009 ; Tromas et al. 2014 ; Donaire, Burgyán, and García-Arenal 2016 ). These authors infected plants with paired viral variants derived from three viruses: TEV, tobacco mosaic virus (TMV), and tomato bushy stunt virus (TBSV); and isolated single protoplast cells from infected leaves at multiple time points.…”
Section: Many (+) Rna Viruses Of Plants Bottleneck Their Populations mentioning
confidence: 99%
“…2009 ; Tromas et al. 2014 ; Donaire, Burgyán, and García-Arenal 2016 ). The authors established that, in the systemically infected plant leaves, successfully infected cells were mostly colonized by fewer than three founding genomes.…”
Section: Many (+) Rna Viruses Of Plants Bottleneck Their Populations mentioning
confidence: 99%